SOME NEW RECORDS ON SPECIES COMPOSITION AND DISTRIBUTION OF TINTINNID CILIATES (ODER TINTINNIDA) IN THE MARINE AREA OF CON CO ISLAND - Nhan, Dinh Van; Thuoc, Chu Van; Cuong, Le Duc (Vietnam Journal of Marine Science and Technology, 2016)
A total of 46 species belonging to 19 genera, 10 families of tintinnids were identified in the coastal waters of Con Co island, of which, 1 family, 5 genera and 14 species were the new records for tintinnids in Vietnamese waters. Family Tintinnidae was the most diverse with 7 genera (accounting for 36% of total genera recorded in studied area) and 13 species (accounting for 28% of total species). Genus Tintinnopsis was the most diverse with 9 species (accounting for 19% of total species). The species composition of Tintinnids was more diverse in the southwest, south and southeast, whereas individual density was more abundant in the west and east of the island. The species composition and density of Tintinnids were more abundant and diverse in offshore area than those in inshore area of the island. The Tintinnid density at the bottom layer was about two times higher than that in the surface layer.